Electrochemical reduction of azo-based chlorotriazine reactive dyes - Guarantini, CCI; Fogg, A. G.; Zanoni, Maria Valnice Boldrin [UNESP]; Ricco, A. J.; Vanyek, P.; Horvai, G.; Silva, A. F. (Electrochemical Society Inc, 1997)
The reduction process of the azo dyes reactive red 120 and reactive green 19 was investigated in B-R buffer pH 2-12 by differential pulse polarography, cyclic voltammetry and controlled potential electrolyse. The reactive red 120 presents two azo groups reducible in a single step of 8 electrons followed by simultaneous reduction of the two clorotriazine groups. The reduction of reactive green 19 is complicated by the presence of azo groups and chlorotriazine moyeties in a non symmetrical molecule. The peaks can be monitored for dyes determination in concentration level up to 1x10(-7) mol/L and 1x10(-9) mol/L using differential pulse polarography or cathodic stripping voltammetry.